Food insecurity among families with infants born during the COVID-19 pandemic in Fortaleza, Northeast Brazil - Simone Farías-Antúnez; Márcia Maria Tavares Machado; Luciano Lima Correia; Hermano Alexandre Lima Rocha; David Augusto Batista Sá Araújo; Maria Suelly Nogueira Pinheiro; Camila Machado Aquino; Ana Luiza Penna; Marcia C. Castro (Journal of Health, Population and Nutrition, 2023)
Abstract Purpose To assess the prevalence of food insecurity (FI) among families with infants born during the COVID-19 pandemic and its associated factors in Fortaleza, the fifth largest city in Brazil. Methods Data from two survey rounds of the Iracema-COVID cohort study collected at 12 (n = 325) and 18 months (n = 331) after birth. FI was measured using the Brazilian Household Food Insecurity Scale. FI levels were described according to potential predictors. Crude and adjusted logistic regressions with robust variance were used to assess factors associated with FI. Results In the 12- and 18-month follow-ups interviews, there was a 66.5% and 57.1% prevalence of FI, respectively. Over the study period, 3.5% of the families persisted in severe FI and 27.4% in mild/moderate FI. Households headed by mothers, with more children, low education and income, sustained maternal common mental disorders, and that were beneficiaries of cash transfer programs were the most affected by persistent FI. Conclusions Although the prevalence of FI decreased in our sample, almost 60% of families in Fortaleza still have no regular access to enough and/or nutritionally appropriate food. We have identified the groups at higher FI risk, which can guide governmental policies.